Localization content of The different varieties of ampalaya (Momordica charantia L.). - Agustin, E. M. (Compendium of Human Ecology Researches in the Philippines, 2003)
Several ampalaya (Momordica charantia L.) varieties namely, Native, Taiwan, Galaxy, Jade Star 1 and 2, Million Green, Verde Buenas, Verde Suerte, OP 01-064, OP 01-127, OP 01-068, and OP 02-367 were tested for the presence of alkaloids in different parts of the fruit and the plant. Thin layer chromatography (TLC) of the crude extracts were made to check for the presence of spots that would correspond to alkaloids. From the precipitation method, negative results were obtained in the pulp while positive results were obtained in the flesh and in the seeds. The seeds of the native variety had higher amounts of alkaloid compared to Galaxy and Taiwan White varieties. Presence of alkaloids was detected in the leaves but not in the same stems for all varieties. Thin layer chromatography showed there is high concentration of alkaloids in the leaves compared to other parts of the plant.